x = [ 16 ± √ (256 - 252) ] / 2
x = [16 ± √ 4) ] / 2
x = 9 , x = 7
2007-11-23 03:41:53
·
answer #1
·
answered by Como 7
·
1⤊
1⤋
x = 16 ±â(16^2-4*63)]/2 = 8±1 = 9, or 7
2007-11-23 00:26:09
·
answer #2
·
answered by sahsjing 7
·
1⤊
0⤋
The Quadratic formula is:
x = [b +/- sq.rt.(b^2 - 4 * a *c)]/2a
So,
x = [16 +/- sq.rt.(256 - 252)]/2
x = [16 +/- sq.rt.(4)]/2
x = [16 +/- 2]/2
x = 7, x = 9
2007-11-23 00:27:52
·
answer #3
·
answered by baseball6z 2
·
0⤊
1⤋
ax²+bx+c=0
x = (-b±sqrt(b²-4ac))/2a
x²-16x+63=0
a = 1
b = -16
c = 63
x = (16±sqrt(16²-4*63))/2
= (16±sqrt(256-252))/2
= (16±sqrt(4))/2
= (16±2)/2
= (8±1)
= {7, 9}
2007-11-23 00:25:42
·
answer #4
·
answered by gudspeling 7
·
0⤊
1⤋
i give u a formula for solving a quadratic equation for general equation
ax^2+bx+c=0
x= [-b+(b^2-4ac)^.5]\2a
x= [-b-(b^2-4ac}^.5]\2a
2007-11-23 01:23:30
·
answer #5
·
answered by avinash s 1
·
0⤊
1⤋
x - 7, 9
Don't need quadratic formula - factor!
2007-11-23 02:02:47
·
answer #6
·
answered by jimbob 6
·
0⤊
2⤋